2019
DOI: 10.1093/jas/skz079
|View full text |Cite
|
Sign up to set email alerts
|

Linseed oil and heated linseed grain supplements have different effects on rumen bacterial community structures and fatty acid profiles in cashmere kids1

Abstract: This study investigated the effects of dietary supplementation with alternative sources of α-linolenic acid on growth, the composition of rumen microbiota, and the interactions between rumen microbiota and long-chain fatty acid (FA) concentrations, in goat kids. Sixty 4-monthold castrated male Albas white cashmere kids (average BW 18.6 ± 0.1 kg) were randomly allocated among three dietary treatments: (i) basal diet without supplementation (Control), (ii) basal diet supplemented with linseed oil (LSO), (iii) ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…Considering that short-chain fatty acids (i.e., VFAs) are the main end products from the carbohydrate catabolism of gut microbes, we sought to explore correlations between the microbial biomarkers identified above and VFAs in the rumen fluid. Similar to the previous findings in goats [18,66] and sheep [14], most microbes were not significantly correlated with VFAs in this study, mainly due to the complex relationships between diet composition, the gut microbiota and metabolic outputs [55,67] (e.g., substrate cross-feeding [68]). However, linear correlations were observed between several microbial taxa (e.g., Veillonellaceae and Succiniclasticum) and VFAs, which were supported by previous work.…”
Section: Discussionsupporting
confidence: 87%
“…Considering that short-chain fatty acids (i.e., VFAs) are the main end products from the carbohydrate catabolism of gut microbes, we sought to explore correlations between the microbial biomarkers identified above and VFAs in the rumen fluid. Similar to the previous findings in goats [18,66] and sheep [14], most microbes were not significantly correlated with VFAs in this study, mainly due to the complex relationships between diet composition, the gut microbiota and metabolic outputs [55,67] (e.g., substrate cross-feeding [68]). However, linear correlations were observed between several microbial taxa (e.g., Veillonellaceae and Succiniclasticum) and VFAs, which were supported by previous work.…”
Section: Discussionsupporting
confidence: 87%
“…The taxonomic assignment of ruminal bacteria in our study revealed that the most abundant phyla were Bacteroidetes and Firmicutes, which was in accordance with the results of previous studies [37,38].The Firmicutes phylum are the main bacteria that degrade bers, including a large number of bacteria which can promote decomposition of cellulose and fermentation of polysaccharides [39]. It was reported that Bulleidia has the capability to utilize saccharides and starch as energy source [40].…”
Section: Discussionsupporting
confidence: 90%
“…It has also been reported that the genus Methanosphaera was H2 utilizing species within the rumen [47]. The genus Fretibacterium was reported to participate in hydrogenation of longchain fatty acid [38]. Thus, the decreased relative abundance of Fretibacterium in the GAS group could be partially attributed to the increased abundance of Methanosphaera.…”
Section: Discussionmentioning
confidence: 88%
“…The taxonomic assignment of ruminal bacteria in our study revealed that the most abundant phyla were Bacteroidetes and Firmicutes, which was in accordance with the results of previous studies [26,27].The Firmicutes phylum are the main bacteria that degrade bers, including a large number of bacteria which can promote decomposition of cellulose and fermentation of polysaccharides [28]. It was reported that Bulleidia has the capability to utilize saccharides and starch as energy source [29].…”
Section: Discussionsupporting
confidence: 90%